Logistical planning standards for responding shelter centres to forced displacement during 2014 aggression in Gaza strip –Palestine - El-Moughgher, Mohammed M.; Mahmud, Mohammed A. (Journal of Risk and Crisis Management, 2020)
Military attacks which repeated on Gaza strip were contributed forced displacement, which causing displaced community to take refuge in shelters. This study was aimed to illustrate the importance and availability of logistical planning standards for responding shelters of displacement in Gaza Strip during 2014 military aggression .The descriptive analytical approach was used by distributing 60 questionnaires as a random sample of workers in centres during 2014. This study explores the importance of logistical planning standards with relative weight (88.74)%, And the availability of logistical planning standards for responding shelters centres in Gaza Strip reached (60.61%), This is a guide for spatial standards according to displace community, nature of land and infrastructure. This research was recommended strengthening logistical planning based on the proper assessment for force-displacement communities, also provide planning and designing standards for land which based on infrastructure, urban structure, social factors, enhancing participatory training, vulnerable groups and people who work together which arranged according to force displacement